Nudge : improving decisions about health, wealth, and happiness - Thaler, Richard H., 1945- (Yale University Press, 2008)
Thaler and Sunstein offer a groundbreaking discussion of how to apply the science of choice to nudge people toward decisions that can improve their lives without restricting their freedom of choice.